Carbon trading system : Model and application for low carbon performance matrix and sustainable development goals alignment - Muhammad Shabir, Shaharudin; Fernando, Yudi; Ganesan, Yuvaraj; Shamil, Abu Hassan (2021)
RO1: Establish a carbon trading mechanism based on the existing literature and sustainable reporting of Malaysian public listed firms. RO2: Software development helps firms identify, measure, report, and benchmark their low carbon performance and align with Sustainable Development Goals(SDGs).